(untitled) (Educação e Pesquisa, 2022)
The article stems from an international scientific cooperation agreement between an Italian public university and a Brazilian federal university to identify and analyze the pedagogical elements that constitute the actions of Brazilian early childhood education teachers in the implementation of non-presential teaching (or remote) in early childhood education institutions, due to the COVID-19 pandemic. The pedagogical elements investigated were educational objectives and intentions, resources, time, and strategies. An electronic survey tool was designed to survey early childhood teachers, containing 44 open and closed questions. Among the 97 respondents, most professionals did not have technical training for the pedagogical use of communication tools or social media, emphasizing the use of WhatsApp® and Facebook®. Such tools were assumed as the primary resources for contact with families and children and to achieve the main intentions: keeping alive the memory of the school routine and the affective relationships with the teachers. Given the pandemic and suspension of face-to-face service in early childhood education, pedagogical practices were redesigned concerning the pedagogical organization, including adapting materials.